What can talent management do about involuntary remote working in the post-COVID-19 era? Spanish IT employees’ organizational commitment - Bermúdez-González, Guillermo José; Lucía-Casademunt, Ana María; Padilla-Angulo, Laura (Springer Nature, 2024)
The purpose of this study is to understand the role of professional isolation and work–family balance (WFB) as talent retention strategies, considering organizational commitment (OC) and the mediating role of job satisfaction (JS) among IT employees in the technological industry have been forced by their companies to telework. While previous research has examined the connections between professional isolation (PI), OC, WFB, and JS separately in the context of teleworking, this research proposes an integrative model examining the connections between all these work-related constructs and allowing for mediating and moderating effects. It focuses on IT employees in the technological industry forced to telework, a setting underexamined by previous literature. The final sample is composed of 294 teleworkers forced to work partly at home by their companies. Partial least squares structural equation modeling (PLS-SEM) was applied, and SmartPLS 4.0.8.7 software was used to analyze the data and test the hypotheses.
Keywords: Pandemia de la Covid-19, 2020-; Teletrabajo; Talent management; Involuntary remote working; Post-COVID-19; Spanish; Organizational commitment